Endgame - Vogel, Hal.; Aukin, David; Milne, Paula; Travis, Pete.; Hurt, William; Ejiofor, Chiwetel, 1977-; Miller, Jonny Lee.; Strong, Mark, 1963-; Jacobi, Derek; Phipps, Martin; Barrett, Ruth, 1954-; Harvey, Robert, 1953-; et al. ([Los Angeles] : Distributed by Monterey Media, 2010)
Working for P. W. Botha, Dr. Neil Barnard opens talks with imprisoned Nelson Mandela. But lesser known are the secret talks that take place in a rural English manor house. Both sides may win or lose all, including their own lives. Botha learns of the British talks and, with the inevitable demise of apartheid, he intends to control the endgame by using the tactics of divide and rule. Against all the odds, a precious arena of frail trust between the two warring parties is achieved
Based on the book "The fall of apartheid" by Robert Harvey
Originally released as a motion picture in 2009
Special features: Interviews with William Hurt & Jonny Lee Miller; interview with director Peter Travis, producer David Aukin & writer Paula Milne. (Features are not rated.)
Director of photography, David Odd ; editors, Clive Barrett, Dominic Strevens ; composers, Martin Phipps, Ruth Barrett
William Hurt, Chiwetel Ejiofor, Jonny Lee Miller, Mark Strong, Derek Jacobi
MPAA rating: PG-13; for violence, disturbing images, and some language
Keywords: Mandela, Nelson, -- 1918-2013. -- Drama; Apartheid -- South Africa -- Drama; International relations -- Decision making -- Drama; South Africa -- Foreign relations -- 20th century -- Drama; South Africa -- Politics and government -- 20th century -- Drama; South Africa -- Social conditions -- Drama; Historical films; Melodramas (Motion pictures).; Video recordings for the hearing impaired; Feature films; Fiction films; DVD-Video discs; Video recordings; Drama